Rheological characterization of Porphyridium sordidum and Porphyridium purpureum exopolysaccharides - Medina-Cabrera, Edilberto Vicente (2021)
Porphyridium exopolysaccharides (EPSs), which contain sulfate and methyl groups, have a similar potential for use in multiple industrial applications as macroalgae counterparts but lack detailed characterization. For this reason, we produced 0.21 g L-1 of P. sordidum EPS and 0.17 g L-1 P. purpureum EPS, followed by a thorough rheological characterization in respect to their differences in monomer composition, sulfate concentrations and methyl patterns. Furthermore, the effect of NaCl and CaCl2 was evaluated, and the effect of high salinity media on the rheological properties of the biopolymers was analyzed. Both Porphyridium EPSs show a remarkable stability at high temperature and under the effect of monoand divalent cations, and high salinity cultivation medium, which was evidenced by the rheological properties of the EPS. This feature is not displayed by many carbohydrate polymers, making it possible to enrich current applications in which EPS are used.